Direct Medical Costs of Pediatric Congenital Heart Disease Surgery in a Belgian University Hospital. Issue 1 (January 2019) - Willems, Ruben; Tack, Philip; François, Katrien; Annemans, Lieven
Objectives: The recent trend to optimize the efficiency of health-care systems requires objective clinical and economic data. European data on the cost of surgical procedures to repair or palliate congenital heart disease in pediatric patients are lacking. Methods: A single-center study was conducted. Bootstrap analysis of variance and bootstrap independent t test assessed the excess direct medical costs associated with minor and major complications in nine surgical procedure types, from a health-care payer perspective. Generalized linear models with log-link function and inverse Gaussian family were used to determine associated covariates with the total hospitalization cost. Descriptive statistics show the repartition between out-of-pocket expenditures and reimbursed costs. Results: Four hundred thirty-seven patients were included. Mean hospitalization costs ranged from €11, 106 (atrial septal defect repair) to €33, 865 (Norwood operation). Operations with major complications yielded excess costs compared to operations with no complications, ranging from €7, 105 (+65.2%) for a truncus arteriosus repair to €27, 438 (+251.7%) for a tetralogy of Fallot repair. Differences in costs were limited between operations with minor versus no complications. Age at procedure, intensive care unit stay, procedure risk category, reintervention, and postoperative mechanical circulatory support were associated with higher total hospitalization costs. Out-of-pocket expenditures represented 6% of total hospitalization costs. Conclusion: Operations with major complications yield excess costs, compared to operations with minor or no complications. Cost data and attribution are important to improve clinical practice in a cost-effective manner. The health-care system benefits from strategies and technological advancements that have an impact on modifiable cost-affecting parameters.